Corticomuscular coherence reflects somatosensory feedback gains during motor adaptation. (June 2018) - Kasuga, Shoko; Momose, Natsumi; Ushiyama, Junichi; Ushiba, Junichi
Highlights: Corticomuscular coherence (CMC) decreased by motor adaptation to novel environment. Long latency reflex responses reflecting feedback gains decreased by adaptation. CMC is suggested to have related function to feedback gains during motor adaptation. Our findings provided a clue for functional meaning of sensorimotor binding. Abstract: Beta-band corticomuscular coherence (CMC) observed between the sensorimotor cortex activity and contracting muscle is declaratively described as a neurophysiological reflection of sensorimotor binding. However, much remains unknown about the functional meaning of 'sensorimotor binding.' The efficacy of information binding in the sensorimotor system is assumed to be influenced by the gain of the feedback controller, which is regulated through a process that may in part be implemented in the primary sensorimotor cortex (SM1). Thus, we predicted that CMC is modulated together with feedback gains during motor learning. We examined this hypothesis using a hand-reaching adaptation task under a novel dynamical environment. CMC modulation was assessed before and after adaptation, and feedback gains were probed by long latency triggered muscle reactions. Overall, we found that CMC significantly decreased during the adaptation period, and such CMC decrease was associated with the decreased long latency reflexes. These results suggest that CMC has a related function to modulation of feedback gains. Our findings provided an electrophysiological hallmark of the sensorimotor binding process, which was stated as a function of CMC but poorly understood.